2003
DOI: 10.1162/089892903321208178
|View full text |Cite
|
Sign up to set email alerts
|

Category-Specific Representations of Social and Nonsocial Knowledge in the Human Prefrontal Cortex

Abstract: Abstract& Complex social behavior and the relatively large size of the prefrontal cortex are arguably two of the characteristics that distinguish humans from other animals. Grafman presented a framework concerning how the prefrontal cortex (PFC) controls complex behavior using stored structured event complexes (SECs). We report behavioral and imaging data from a modified go/no-go paradigm in which subjects had to classify words (semantic) and phrases (SEC) according to category. In experimental trials, subject… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
27
0
1

Year Published

2004
2004
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 61 publications
(29 citation statements)
references
References 62 publications
1
27
0
1
Order By: Relevance
“…Some have argued that mentalizing processes mediated by the LIFG, a component of the mirror neuron system [Rizzolati and Craighero, 2004], may enable the understanding of others through simulation [i.e., ''putting oneself in another's shoes''; Gallese and Goldman, 1998]. In a different vein, however, the LMFG/LIFG has long been known to be important for verbal working memory [Gabrieli et al, 1998], and two recent studies demonstrated the LMFG's and LIFG's selective engagement for representing social (rather than nonsocial) knowledge and abstract social concepts [Wood et al, 2003;Zahn et al, 2007]. These would suggest that the LMFG/LIFG's role in individuated judgments may correspond with an increased representation of social information (e.g., personalized details about others).…”
Section: Discussionmentioning
confidence: 99%
“…Some have argued that mentalizing processes mediated by the LIFG, a component of the mirror neuron system [Rizzolati and Craighero, 2004], may enable the understanding of others through simulation [i.e., ''putting oneself in another's shoes''; Gallese and Goldman, 1998]. In a different vein, however, the LMFG/LIFG has long been known to be important for verbal working memory [Gabrieli et al, 1998], and two recent studies demonstrated the LMFG's and LIFG's selective engagement for representing social (rather than nonsocial) knowledge and abstract social concepts [Wood et al, 2003;Zahn et al, 2007]. These would suggest that the LMFG/LIFG's role in individuated judgments may correspond with an increased representation of social information (e.g., personalized details about others).…”
Section: Discussionmentioning
confidence: 99%
“…This corresponds to an overall alpha level of P<0.05 corrected for multiple comparisons as calculated by the Monte Carlo simulation and method of Forman et al (1995) implemented in AFNI, which has been employed in numerous prior studies (e.g. Konishi et al, 1998;Poldrack et al, 1999;Ochsner et al, 2004a;Wagner, 1999;Wood et al, 2003). Two different analyses were used to identify regions whose activation correlated with fear of pain and anxiety sensitivity.…”
Section: Discussionmentioning
confidence: 99%
“…This region is considered necessary for decision making, particularly in evaluating the consequence of decisions [55] . It has also been proposed that knowledge of social events and rules is stored in this area of the neocortex [56,57] . Thus, the patients' improper behavior while driving might reflect the loss of functions mediated by this region.…”
Section: Discussionmentioning
confidence: 99%